M18 The Relationship between anxiety and depression to exacerbations of COPD resulting in hospital admissions; a narrative systematic review. (14th November 2013) - Pooler, A; Beech, R
Abstract : Introduction and Objectives: Exacerbations because of COPD are the third largest cause of emergency hospital admissions in the UK. This systematic literature review explored the relationshipbetween hospitalisation rates and the COPD co-morbidities, anxiety and depression. Methods: The Centre for Research Dissemination's framework for systematic reviews was followed using search terms relating to COPD, anxiety, depression and hospital admission. Papers identified were assessed for relevance and quality using a suitable CASP tool and the Mixed Methods Assessment Tool (MMAT). Results: Quantitative studies (18) indicated that anxiety and depression led to a statistically significant increase in the likelihood of COPD patients being hospitalised. These co-morbidities also led to an increased length of stay and a greater risk of mortality post discharge. Other significant factors included lower BODE scores, female gender, lower socioeconomic status, poorer patient perceived quality of life, increased severity of lung function and less improvement in dyspnoea from admission to discharge. It was also highlighted that only 27–33% of those with depression were being treated for it. Qualitative studies (6), revealed that patients saw anxiety and depression as a major factor that affected their ability to cope with and self-manage their condition. Implications: Findings from the systematic review have highlighted a need for better recognition and treatment of anxiety and depression amongst individuals with COPD. On-going research will develop and test strategies for promoting better management and self-management as a means of reducing hospital admissions.